The State of Actin Polymerization in Tetracaine-Treated Platelets - Davies, Gregg E; Palek, Jiri (Thrombosis and Haemostasis, 1982)
Although there is considerable evidence that platelet activation is associated with polymerization of actin, it is not known whether there is some pre-existing F-actin even before activation. We have examined the state of actin polymerization in nonactivated platelets by deoxyribonuclease assay of G-actin and total actin. To fully suppress activation, platelets were prepared in the presence of tetracaine. The G-actin/total actin ratio in tetracaine-treated platelets prepared by three different methods is significantly less than one (average of all results = 0.61). We conclude that about 39% of total actin in nonactivated tetracaine-treated platelets may be present as F-actin.
Keywords: Actin polymerization; Tetracaine-treated platelets